(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The objective of this research is to determine the effect of microwave furnaces heat energy on the surface of an aluminum alloy AA 6061-T6, also, to investigate the range of change in mechanical properties and the estimated fatigue life have through different medium (dry and salt solution) and duration times (0.5-1 hour). It was found that the heat generated by the energy of the microwave furnace affected the ultimate stress and the yield stress as well as surface roughness, hardness and modulus of elasticity, where degrees varied according to the time of exposure to those waves. The estimate fatigue life was also affected by heat generated through the energy of the microwave furnace. The highest range of change was when the alloy specimen was subjected to microwave heat energy for one hour. All the variation was compared with the properties of the alloy without treatments as received (ASTM Standards) in tables within the research. Also, the research aims to change the wrong idea about not using metals with the microwaves furnace and to prove it’s safe to do that through controlled steps.